Perspectives in Asian Rhinoplasty - Jang, Yong Ju; Yi, Jong Sook (Facial Plastic Surgery, 2014)
Asian patients present with relatively poorly developed dorsal and tip height and thicker skin, so augmentation rhinoplasty is the most commonly performed rhinoplasty procedure. Tip surgery using autologous cartilage followed by dorsal augmentation using an alloplastic implant material is the most widely performed surgical procedure for augmentation rhinoplasty on Asian patients. Cartilage tip grafting procedures, including shield grafting, multilayer tip grafting, onlay grafting, and modified vertical dome division, are key maneuvers for building up and providing better definition on a relatively poorly developed Asian tip. When performing primary cosmetic dorsal augmentation using alloplastic implants, the implant material should be selected according to the surgeon's experience, the pros and cons of available dorsal implant materials, and host factors such as skin thickness, associated deformities, and aesthetic goals. The costal cartilage is best reserved for difficult revisions, except in a limited number of primary cases who present with a very poorly developed nasal skeleton and thick skin.
Keywords: Asian rhinoplasty; tip surgery; dorsal augmentation; graft materials